The National and Cultural Specifics of the Verbalization of the “Anti-Terrorism Measures” Concept Sphere in English and Russian Linguocultures - I. A. Vezner; I. V. Lisitsa (Дискурс)
Introduction. The method of cognitive-conceptual modeling is becoming increasingly important in analysing discursive phenomena and it allows to identify both universal and ethnocultural content of concept spheres as well as to characterize the linguistic means of their verbalization. The application of this method allows the authors of the paper to describe the means of discursive representation of the concept sphere ‘anti-terrorism measures’ in English and Russian linguocultures. The paper attempts to identify conceptually significant features of the configuration of the concept sphere under analysis.Methodology and sources. Conceptually significant features and the specifics of their configuration are examined as the verbal objectification of social interaction, influenced by a range of cultural factors. The linguistic material comprises handouts, guides, and manuals from websites, as well as anti-terrorism guides, manuals, and instructions placed in educational institutions and public transport in Novosibirsk. The authors employed such methods as information and semantic text analysis, cognitive-comparative modelling of the concept sphere, genre-discursive and comparative analyses.Results and discussion. The analysis identified the following fundamental concepts that objectify the concept sphere “anti-terrorism measures”: “a subject countering terrorist activity”, “a probable subject of terrorist activity”, “prescribed actions and measures to prevent a terrorist attack”, “probable actions of hostages”, “probable actions after a terrorist attack”. In the English linguoculture, the texts that can be attributed to strongly preventive genres of anti-terrorist discourse prevail. In Russian linguoculture, anti-terrorist materials mainly present the situations at a later stage of a terrorist attack; they are characterized by joint verbalization of the concepts ‘vertical integration’ and ‘centralization’.Conclusion. The research results indicate that the examined anti-terrorism materials possess a number of culturally determined conceptual features based on the following oppositions: “highly preventive – weakly preventive”, “horizontally integrated community – vertically integrated community”, and “decentralization – centralization”.